2005
DOI: 10.1242/jeb.01508
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional antennal lobe atlas of male and female moths, Lobesia botrana (Lepidoptera: Tortricidae) and glomerular representation of plant volatiles in females

Abstract: Spatiotemporal odour coding is thought to be linked closely with the specific glomerular anatomy of the primary olfactory centre. In most insects the number of the glomeruli within the antennal lobe is limited to fewer than 100, allowing their individual identification. In the grapevine moth, Lobesia botrana, a map of the antennal lobe glomeruli was reconstructed three-dimensionally, by comparing three different brains in males and females. The map of the antennal lobe of females served then as a basis to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 63 publications
(86 reference statements)
4
53
2
Order By: Relevance
“…In parallel, we will present, as a reference, data from uniglomerular projection neurons (uPNs). Projection neurons generate Na ϩ -driven action potentials, and their morphology and response properties are well known in the cockroach (Burrows et al, 1982;Ernst and Boeckh, 1983;Boeckh and Ernst, 1987;Malun et al, 1993;Distler and Boeckh, 1997a) and other insects [Apis mellifera (Sun et al, 1997;Abel et al, 2001), Drosophila melanogaster (Wilson et al, 2004), Schistocerca americana (Wehr and Laurent, 1996;Stopfer and Laurent, 1999;Stopfer et al, 2003;Bazhenov et al, 2005;Broome et al, 2006), and different moths (Waldrop et al, 1987;Kanzaki et al, 1989;Hansson et al, 1994;Masante-Roca et al, 2005;Namiki et al, 2008)]. In the second part, we present a detailed analysis of the voltage-activated Ca 2ϩ currents in two physiologically different LN types and uPNs.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, we will present, as a reference, data from uniglomerular projection neurons (uPNs). Projection neurons generate Na ϩ -driven action potentials, and their morphology and response properties are well known in the cockroach (Burrows et al, 1982;Ernst and Boeckh, 1983;Boeckh and Ernst, 1987;Malun et al, 1993;Distler and Boeckh, 1997a) and other insects [Apis mellifera (Sun et al, 1997;Abel et al, 2001), Drosophila melanogaster (Wilson et al, 2004), Schistocerca americana (Wehr and Laurent, 1996;Stopfer and Laurent, 1999;Stopfer et al, 2003;Bazhenov et al, 2005;Broome et al, 2006), and different moths (Waldrop et al, 1987;Kanzaki et al, 1989;Hansson et al, 1994;Masante-Roca et al, 2005;Namiki et al, 2008)]. In the second part, we present a detailed analysis of the voltage-activated Ca 2ϩ currents in two physiologically different LN types and uPNs.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, however, neither of these studies measured the doseresponse characteristics of the neurons. Recently, Masante-Roca et al (2005), based on findings in two animals, reported that PNs thought to arborize in the same glomerulus responded to different odor stimuli. Here, we found that G35-PNs could respond to other stimuli in addition to c3HA at high concentrations, but their specificity was higher at lower stimulus concentrations (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The glomeruli are organized chemotopically [i.e., each glomerulus is a functional unit dedicated to processing information about a particular odor compound or molecular attribute(s) of odor compounds] (for review, see Buck, 1996;Hildebrand and Shepherd, 1997). The mammalian OB includes Ͼ1000 glomeruli (Mombaerts et al, 1996), whereas the AL of most insects has only 40 -160 glomeruli, depending on the species (Flanagan and Mercer, 1989;Hildebrand, 1992, 2000;Berg et al, 2002;Masante-Roca et al, 2005). Thus, because of its numerical simplicity and the possibility of identifying glomeruli across individuals, the insect AL is an advantageous model for studies of glomerular function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, male insects have sex specific glomeruli, the macroglomerular complex, which exclusively process information regarding sex pheromones released by conspecific females (cockroach: Burrows et al, 1982;moth: Christensen and Hildebrand, 1987;Kanzaki et al, 1989; fly: Kondoh, 2003;Stockinger et al, 2005). Further, in the moth, female specific glomeruli process odor information concerning host plants ( Masante-Roca et al, 2005;Skiri et al, 2005). On the other hand, like crickets some insects have no macroglomerulus (e.g.…”
Section: Terminal Of Antennal Sensory Afferentsmentioning
confidence: 99%